Effect of sugar and starch on chemical and organoleptic parameters of pineapple bar during storage (Progressive Agriculture, 2019)
The aim of this study was to assess the effect of major ingredients on the changes of fundamental quality parameters of pineapple fruit bar during preparation and storage.  Four samples were prepared by using Extreme Vertex mixture taking three major ingredients namely fruit pulp, sugar and starch content as factors and non-enzymatic browning data and overall acceptability as responses. The result revealed that compositional differences of different ingredients in formulation fitted to the quadratic linear model at   p